Implementation of Electronic KTP (E-KTP) Services in the Era of New Habit Adaptation (AKB) of the Population and Civil Registration Service (DINDUKCAPIL) of Pekalongan City, Central Java - Maya Sofiana; Endang Supriyadi; Rita Wahyuni (Majalah Ilmiah Bijak, 2021)
Population administration services are one of the government's general duties in terms of public services. The activities of managing and controlling data and publishing population documents are part of population administration. In this case the Electronic Identity Card (E-KTP) is the legal identity of the resident in which individual data is contained. However, in its application in the field, the E-KTP service still has obstacles so that it is not maximally felt by the people. As for the obstacles found in E-KTP services, among others, in terms of personnel, namely the lack of optimal service provided can be from the aspect of behavior caused by  time limit or work pressures so that it affects the quality of service besides that in terms of lack of infrastructure or disruption of equipment such as server connections and limited blanks, and lack of clear information for the general public. The government's latest policy is rolling so that the people can tolerate with Covid-19. Based on recommendations of the World Health Organizations (WHO), the recommendation of a New Normal is not only trending around the world. then the recommendation in Indonesia changed to "Era of Adaptation to The New Habits", the meaning of the recommendation  can be interpretated to be a new life order, not returning to a life likes the pandemic era but obliged to be accustomed to washing hands  by using soap, using masks, maintaining physical distance, and maintaing body imune. This has an impact on public services, people feel inconvenience in public administration services. In fact, referring to the law, the people is obliged to get good public services. Research methods . The research method using in this research is qualitative with a phenomenological approach in which the researcher can explain objectively based on the experiences of a group of individuals relating to the practice in the field that relates to the implementation of E-KTP services in the Era of The New Habitual Adaptation (AKB) at the Department Population and Civil Registration (DINDUKCAPIL) Pekalongan City, Central Java. The technique of collecting data through observation, interviews, documentation, literature, websites. The data analysis using is interactive analysis are cyclical and interactive process. This analysis include 4 components: data collection, data reduction, data presentation, and drawing conclusions or verification. Targeted output . It is in the form of scientific publications in the ISSN National Journal to be submitted, speakers in registered scientific meetings, teaching materials (ISBN) drafts, and published newspaper articles. TKT of research proposed is TKT 1 basic research